Nano iron porphyrinated poly (Amidoamine) dendrimer MCM-41 for extraction of nitrosamines and poly (Ethanolamine) dendron for detection of selected metals in aqueous samples - Chong, Mun Hwa, 1985- , author; Mohd. Marsin Sanagi, supervisor; Salasiah Endud, supervisor; Fakulti Sains (2015)
Thesis (Ph.D (Kimia)) - Universiti Teknologi Malaysia, 2015